MEDICAL AND SOCIAL FEATURES OF LASER EYE INJURIES IN MILITARY PERSONNEL OF THE DEFENSE FORCES OF UKRAINE - Badiuk, M.I.; Zhupan, B.B.; Khramov, I.I.; Mykyta, O.O. (World of Medicine and Biology, 2023)
For the first time, an analysis of tactical and medico-social features of combat damage to the organ of sight in the Defense Forces of Ukraine servicemen from field tactical lasers was conducted using open-world sources of scientific information. The medical and tactical characteristics of admission of victims to specialized healthcare facilities are given, and complaints, medical history, and clinical features of laser injuries are revealed. It was noted that 2/3 of the lesions were monocular. The direct dependence of the severity of the lesion on the distance to the laser beam source was proved. Macular ruptures, manifested severe retinal lesions, and central or paracentral scotoma were noted. All patients with eye injuries underwent conservative treatment. In 25 % of cases, surgical interventions were performed. After treatment and rehabilitation, the servicemen underwent a military medical examination; 50 % remained fit to perform their military service duties.